Evaluation of the increased risk of spine fracture in patients with mood disorder compared with matched controls: a longitudinal follow-up study using a national sample cohort in Korea - Hyo Geun Choi; Miyoung Kim; So Young Kim; Chanyang Min; Bumjung Park (BMJ Open)
Objective To evaluate the risk of spine fracture in patients with mood disorder using a nationwide cohort.Design A longitudinal follow-up study.Setting Claims data for the population ≥20 years of age were collected from 2002 to 2013 for the Korean National Health Insurance Service-National Sample Cohort.Participants A total of 60 140 individuals with mood disorder were matched with 240 560 individuals (control group) for age, sex, income, region of residence and osteoporosis.Interventions In both the mood disorder and control groups, the history of spine fracture was evaluated. The International Classification of Diseases 10th Revision codes for mood disorder (F31–F39) and spine fracture (S220 and S320) were included.Primary and secondary outcome measures The univariable and multivariable HRs and 95% CIs of spine fracture for patients with mood disorder were analysed using a stratified Cox proportional hazards model. Subgroup analyses were conducted according to the history of osteoporosis, age and sex.Results Approximately 3.3% (2011/60 140) of patients in the mood disorder group and 2.8% (6795/240 560) of individuals in the control group had spine fracture (p<0.001). The mood disorder group demonstrated a higher adjusted HR for spine fracture than the control group (multivariable HR=1.10, 95% CI 1.04 to 1.15, p<0.001). The participants without osteoporosis showed a higher HR of mood disorder for spine fracture than the control participants (multivariable HR=1.25, 95% CI 1.14 to 1.37, p<0.001). According to age and sex, this result was consistent in subgroups of women aged 20–39 and 40–59 years and men aged ≥60 years.Conclusion The risk of spine fracture was increased in patients with mood disorder. The potential risk of spine fracture needs to be evaluated when managing patients with mood disorder.